Exports and economic growth nexus: the case of Pakistan - Nasim , Shah Shirazi; Turkhan Ali , Abdul Manap (Pakistan Institute of Development Economics, 2004)

(untitled)
This paper re-investigates the exports and economic growth nexus for Pakistan. The paper employs cointegration and multivariate Granger Causality Test [Toda and Yamamoto (1995)] to study the long-run and short-run dynamics among exports, imports, and real output growth over the 1960–2003 period. Results strongly support a long-run relationship among imports, exports, and output growth. Feedback effect between import and output growth and unidirectional causality from export to output growth was found. Nevertheless, the results do not confirm any significant causality between imports and exports.